2021
DOI: 10.3390/logistics5020031
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Omni-Channels for Customer-Centric e-Tailing

Abstract: In this volatile post-COVID environment where customers look for ways to order products online using personal computers and mobile devices, a traditional sale/delivery of products via single distribution channel needs to be reassessed. As a revolutionary alternative to a conventional distribution channel, this paper proposes an omni-channel strategy. The omni-channel aims to maximize the customer shopping experience by diversifying and integrating the product purchase and delivery media through customer engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some research directly addresses omnichannel loyalty and the omnichannel experience to reinforce that good omnichannel performance directly impacts customer loyalty and experience (Peltola et al, 2015;Simone and Sabbadin, 2017;Yadav et al, 2017). It can be assumed that good omnichannel performance seeks to improve the customer experience and customer loyalty as the ultimate goal (Kumar et al, 2019;Larke et al, 2018;Min, 2021). Thus, this research hypothesizes that: H6.…”
Section: Omnichannel Managementmentioning
confidence: 95%
“…Some research directly addresses omnichannel loyalty and the omnichannel experience to reinforce that good omnichannel performance directly impacts customer loyalty and experience (Peltola et al, 2015;Simone and Sabbadin, 2017;Yadav et al, 2017). It can be assumed that good omnichannel performance seeks to improve the customer experience and customer loyalty as the ultimate goal (Kumar et al, 2019;Larke et al, 2018;Min, 2021). Thus, this research hypothesizes that: H6.…”
Section: Omnichannel Managementmentioning
confidence: 95%
“…Digitization can facilitate the omnichannel business from the improvement of omnichannel retail (Ishfaq et al, 2022). Omnichannel retail allows consumers to access the whole available shopping channels, such as mobile internet devices, computers, in-store, and television (Min, 2021). Consumers can playfully adopt healthcare wearable devices by comparing products in all different available retail channels and tracking order deliveries in time through digitalized product flows if they purchased a product from the online platform.…”
Section: Digitalization In Healthcarementioning
confidence: 99%
“…It also indicates the implementation of different channels to interact with customers precisely due to a unified operation, where customers can interact with the business seamlessly. In other words, an omnichannel environment is an integrated strategy where customers can seek information and purchase through various channels simultaneously (Min, 2021). Past research has shown that this perfect integration across channels could promote customer experiences and business performance (Mirzabeiki & Saghiri, 2020;Bijmolt et al, 2021).…”
Section: Omnichannel In the Healthcare Businessmentioning
confidence: 99%
“…7P marketing mix, which can be defined as a set of fundamental variables that strategists should decide on, is seen as the second most appeared sub-sub-theme. Herein, topics like price regulations and gouging (Chakraborti and Roberts, 2021), product characteristics (Harjadi, et al, 2020), marketing implications of 7P (Das, Jain, et al, 2021), advertising strategy (Robinson and Veresiu, 2021) and omni channels (Min, 2021;Verhoef, 2021) were studied. Furthermore, it is seen that social media and communication were studied as much as the 7P marketing mix as well.…”
Section: Marketingmentioning
confidence: 99%
“…Moreover, concepts like ambiguity (Gunessee and Subramanian, 2020), coordination (Yadav, et al, 2020), green supply chain (Fasan, et al, 2021), distribution channels (Min, 2021), and logistics performance (Qin, et al, 2021) was focused on. In further studies, since the increase in emphasis on the redesign of supply chains is considered, it would be meaningful to study omni-channels more by considering specific sectors/organizations.…”
Section: Supply Chain Managementmentioning
confidence: 99%